Организационно-экономические механизмы управления инновационным развитием отечественных предприятий. (Путеводитель предпринимателя, 2020)
In article new requirements to administrative activity in the light of an innovative orientation of modern economic processes are reflected. The model, allowing to solve a problem of use of constantly increasing volumes and a variety of knowledge involved in innovative processes taking into account their transformation in the course of innovative activity of the domestic enterprises is offered.